Pengaruh Pemberian Berbagai Jenis Alkohol saat Marinasi terhadap Kandungan Lemak, Aroma, dan Rasa Na’an Maran - Adelfita Bisilisin; Gemini E. M. Malelak; Geertruida M. Sipahelut (Student Scientific Creativity Journal, 2026)
This study aims to determine the fat content, aroma, and taste of na’an maran treated with various types of alcohol. The research method used was a completely randomized design (CRD) with 4 treatments and 4 replicates. The treatments consisted of P0 = 1 kg beef + 2% salt (without added alcohol), P1 = 1 kg beef + 2% salt + 10% beer, P2 = 1 kg beef + 2% salt + 10% red wine, and P3 = 1 kg beef + 2% salt + 10% Sophia. The variables studied were fat content, aroma, and flavor. The results showed that the addition of various types of alcohol had a highly significant effect (P < 0.05) on the aroma, flavor, and fat content of fresh meat, as well as a non-significant effect (P > 0.05) on the fat content of na’an maran. Among the different types of alcohol administered at the same concentration, the best results were obtained in P0 (without added alcohol) for aroma and taste, and it also reduced the fat content. In conclusion, the addition of various types of alcohol at the same concentration caused the meat’s characteristic aroma to disappear and the taste score to decrease, though the meat was still considered tasty. The fat content of na’an maran was not affected by alcohol; however, Sophia caused the fat content of fresh meat to increase, while beer and wine caused it to decrease.